Nature vs nurture: learning conceptions and environment as precursors to learning strategy patterns and their outcomes. Issue 7 (10th November 2022) - Shum, Alex; Fryer, Luke K.; Cano, Francisco; Berbén, Ana Belen García; Pichardo-Martínez, M. Carmen
ABSTRACT: Much of formal higher education research on learning experiences has focused on processing strategies and outcomes, however, less attention has been paid to their precursors. This study employed Biggs' 3P model to examine the contributions of learning conceptions (as part of learning patterns (LPs) research; construction of knowledge, intake of knowledge) and perceptions of learning environment (appropriate workload, good teaching) as Presage factors affecting both (stepwise, deep) processing and (self-, external, lack of) regulation strategies (Process), which collectively affect outcomes (Product; generic skills, satisfaction, and end-of-term grade). Psychology students ( n = 242) in second and third year attending a major state-supported university completed the Inventory of Learning Styles, the Course Experience Questionnaire and student satisfaction of teaching scale. Fully-forward latent-variable SEM was undertaken according to the stages of the 3P model. Though some relationships in part reflected meaning-directed (construction of knowledge predicting deep processing and self-regulation) and reproduction-directed (intake of knowledge predicting stepwise processing and external regulation) LPs, several associations did not support traditional learning patterns (construction of knowledge predicting external regulation, intake of knowledge predicting lack of regulation). The results warrant the continued investigation of these relationships between learning components of LPs using more robust research designs and analyses. A positive learning environment (appropriate workload) predicted deep processing and negatively predicted lack of regulation. Deep processing positively predicted achievement while lack of regulation negatively predicted all outcomes. Learning conceptions and learning environment simultaneously had large effects on learning strategies and outcomes, indicating the importance of supporting their development. A separate Latent Profile Analysis of Presage variables revealed three subgroups: Inactive, Passive-Idealist and Environment Driven; none of which revealed a preference for either construction or intake of knowledge. Learning environment positively associated with achievement. Theoretical and practical implications are discussed.